Find the inverse function in slope-intercept form (mx+b):
2 answers:
Answer:
y=(-x/3)+3
Step-by-step explanation:
y=-3x+9
x=-3y+9
x-9=-3y, next division
(x-9)/-3=y
simply and rearrange
y=(-x/3)+3
Answer:
y= 3- x/3
Step-by-step explanation:
To find the inverse function, swap x and y, and solve the resulting equation for x.
If the initial function is not one-to-one, then there will be more than one inverse.
So, swap the variables: y=9−3x so it becomes x=9−3y.
Now, solve the equation x=9−3y for y. You would just need to leave y alone so you divide by 3 on both sides (NOT negative 3. Just 3.)
You might be interested in
Answer:
10
Step-by-step explanation:
-80 / -8 = 10
the negatives cancel each other out
Check the picture below.
![\bf 0=AB^2+6AB-121\implies \stackrel{\textit{using the quadratic formula}}{AB=\cfrac{-6 \pm \sqrt{6^2-4(1)(-121)}}{2(1)}} \\\\\\ AB=\cfrac{-6 \pm \sqrt{520}}{2}\implies AB=\cfrac{-6 \pm \sqrt{4\cdot 130}}{2} \\\\\\ AB=\cfrac{-6 \pm \sqrt{2^2\cdot 130}}{2}\implies AB=\cfrac{-6 \pm 2\sqrt{130}}{2} \\\\\\ AB=-3\pm\sqrt{130}\implies AB= \begin{cases} \boxed{-3+\sqrt{130}}\\\\ -3-\sqrt{130} \end{cases}](https://tex.z-dn.net/?f=%5Cbf%200%3DAB%5E2%2B6AB-121%5Cimplies%20%5Cstackrel%7B%5Ctextit%7Busing%20the%20quadratic%20formula%7D%7D%7BAB%3D%5Ccfrac%7B-6%20%5Cpm%20%5Csqrt%7B6%5E2-4%281%29%28-121%29%7D%7D%7B2%281%29%7D%7D%0A%5C%5C%5C%5C%5C%5C%0AAB%3D%5Ccfrac%7B-6%20%5Cpm%20%5Csqrt%7B520%7D%7D%7B2%7D%5Cimplies%20AB%3D%5Ccfrac%7B-6%20%5Cpm%20%5Csqrt%7B4%5Ccdot%20130%7D%7D%7B2%7D%0A%5C%5C%5C%5C%5C%5C%0AAB%3D%5Ccfrac%7B-6%20%5Cpm%20%5Csqrt%7B2%5E2%5Ccdot%20130%7D%7D%7B2%7D%5Cimplies%20AB%3D%5Ccfrac%7B-6%20%5Cpm%202%5Csqrt%7B130%7D%7D%7B2%7D%0A%5C%5C%5C%5C%5C%5C%0AAB%3D-3%5Cpm%5Csqrt%7B130%7D%5Cimplies%20AB%3D%0A%5Cbegin%7Bcases%7D%0A%5Cboxed%7B-3%2B%5Csqrt%7B130%7D%7D%5C%5C%5C%5C%0A-3-%5Csqrt%7B130%7D%0A%5Cend%7Bcases%7D)
since the distance AB cannot be a negative value, thus is not -3-√(130).
Answer: 0.61, 5/8, 0.95
Step-by-step explanation:
Answer:
14x +2
Step-by-step explanation:
(8x + 6x) +3 -5 = (14x) +3-5
14x (+ 3-5) = 14x (+ 2)